'An Uneasy Truth?': Female Tourism Managers and Organizational Gender Equality Measures in Portugal - Bakas, Fiona (2018)
Drawing on the theme of gender equality in tourism, this book aims to identify the main obstacles to women's advancement in the tourism industry, and to discover and share successful strategies to overcome them, drawing on case studies from all over the world. Interlaced between the 12 chapters of the book are stories from women who work in tourism. The chapters and stories that make up this book explore women's stories of empowerment beyond the neoliberal conceptualizations of economic improvement, to highlight the structural inequalities that prevent true gender equality. The collection points to the slow and small changes that women are making and how women are using the transformations tourism brings to their advantage. The book has a subject index.